World Workshop on Oral Medicine VII: Targeting the microbiome for oral medicine specialists—Part 1. A methodological guide. (29th May 2019) - Varoni, Elena M.; Bavarian, Roxanne; Robledo‐Sierra, Jairo; Porat Ben‐Amy, Dalit; Wade, William G.; Paster, Bruce; Kerr, Ross; Peterson, Douglas E.; Frandsen Lau, Ellen
Abstract: Advances in high‐throughput sequencing technologies have allowed for a rapid increase in knowledge about the human microbiome in both healthy and diseased states, which is expected to increase our understanding of multifactorial diseases. The World Workshop on Oral Medicine VII chose the microbiome as one of its topics of focus. Part 1 of this review provides updated knowledge in the field of microbiome research, describes the advantages and disadvantages of currently available sequencing technologies, and proposes a seven‐step "recipe" for designing and performing studies that is supported by contemporary evidence. Part 2 of this review in a companion paper discusses the results of high‐throughput sequencing studies published to date on the microbiota associated with oral mucosal diseases. The goal of this collective enterprise is to encourage more oral medicine specialists to become engaged in multidisciplinary collaborations to investigate the role of the microbiome in relation to oral diseases, which could potentially lead to enhanced diagnosis, risk assessment and treatment of these patients.